Development of Learning Media to Improve Learning Achievement (Study on Physical Education, Sports and Health (PJOK) Class III Subjects at SD Negeri Kota Bengkulu) - Hadi, Isratul (Indonesian Journal of Sport, Health and Physical Education Science, 2024)
This study set out to identify the phases involved in developing multimedia for PJOK learning, assess the viability of using multimedia in PJOK learning, and evaluate the efficiency of learning media in Class III instruction at Bengkulu City State Elementary School. Bengkulu City State Elementary School class III participated in this study, which employs a development research strategy (Research and Development). The goal of this research on multimedia development is to use Microsoft Office PowerPoint software to create educational materials for Bengkulu City State Elementary School's PJOK Learning program. The methods used to gather data are documentation, assessment questions, surveys, and observation. methods for data analysis applied to the distribution of percentages and scores against preset categories on the rating scale. Learning materials with multimedia included on a CD (compact disk) constitute the study's output. The media expert evaluation yielded an overall percentage of 82.4%, the material expert produced a total percentage of 92.85%, the limited test produced a total percentage of 82.81%, and the widespread test produced a total percentage of 80.1%. This educational tool has demonstrated its ability to raise student learning outcomes. The experimental class had an average score of 80.62, whereas the control class received an average of 76.52. Based on the test findings above, it is possible to infer that the learning media created is useful for raising student learning accomplishment and practical to use as a learning support in PJOK learning.